Crystal structure, microstructure, and ultra-high energy storage properties of lead-free (x)Bi(Mg0.5Ti0.5O3-(1-x)[0.50Ba(Zr0.2Ti0.8)O3-0.50(Ba0.7Ca0.3)TiO3] ternary ceramics - Pal V.; Kumar D.; Singh A.K. (My University, 2025)
In recent times, advance electronics demand high energy storage materials that work efficiently for next-generation devices. Herein, a novel ternary lead-free (x)Bi(Mg0.5Ti0.5)O3–(1-x)[0.50Ba(Zr0.2Ti0.8)O3-0.50(Ba0.7Ca0.3)TiO3] solid solution with x ≤ 0.10, ceramic energy storage materials were prepared by high energy ball milling method. The crystal structure, ferroelectric, and energy storage response were investigated in detail. The X-ray diffraction characterization confirms the single-phase perovskite cubic structure for x ≤ 0.10. Dense, pore-free, and homogeneous microstructures were obtained in these samples. The average grain size decreased with increasing ‘x’ due to grain growth inhibition. The developed compositions exhibit significantly improved break-down strength with strong frequency dispersion in εr and tanδ. Slim polarization (P)-Electric field (E) hysteresis loops were obtained for x ≤ 0.10. The composition x = 0.075 exhibits ultra-high energy storage efficiency (ɳ) (∼81 %) and large recoverable energy density (Wrec) (0.276 J/cm3) which makes it a potential candidate for various applications that require high energy density capacitors. © 2022 Elsevier B.V.